Constitutional Perspective of Human Rights Values in Local Wisdom in the Special Region of Yogyakarta (Study of Constitutional Court Decision No. 88/PUU-XIV/2016) - Triwahyuningsih Triwahyuningsih; Siti Zuliyah; Uni Tsulasi Putri; Hanifah Febriani; Zulfiani Ayu Astutik (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose: This research aims to (1) explore the local wisdom values of the Special Region of Yogyakarta (DIY), which can constitutionally strengthen human rights values in Indonesia, and (2) analyze the judge's consideration of the Constitutional Court Decision No. 88/PUU-XIV/2016 from the perspective of universalism versus particularism of human rights in Indonesia. Methodology: This normative legal research employed a philosophical and statutory approach. This research used only secondary data consisting of primary and secondary legal materials refined through Focus Group Discussion. The data were then analyzed by descriptive qualitative philosophy to find the meaning behind the object under study through data reduction, classification, interpretation, display, and drawing conclusions. Results: The study revealed that (1) constitutional human rights values in DIY’s local wisdom are explicitly stated in the DIY Regional Regulations (Perda) and Special Regional Regulations (Perdais). DIY’s local wisdom can philosophically strengthen human rights values in Indonesia based on Pancasila, confirming that Pancasila as a constitutional identity crystallizes cultural customs and religious values throughout Indonesia. (2) The judges’ opinion for the Constitutional Court Decision No. 88/PUU-XIV/2016 is relative-particular; other than human rights is universal as there is no differentiation between the male and female to be the Governor of Yogyakarta Special Region, in the particular case of Yogyakarta, it remains upholding the local wisdom values as the requirement to be the Governor of Yogyakarta Special Region, where he shall be the reigning monarch of Sultan Hamengku Buwono, and the requirement to be the Sultan relies on the hereditary internal law of the Kasultanan Ngayogyakarta Hadiningrat (Yogyakarta Palace) since 1755. Applications of the study: This study is applied (1) to maintain and preserve the local wisdom values of the Special Region of Yogyakarta (DIY) for the upholding of human rights in Indonesia as mandated by the 1945 Constitution and (2) to support the government’s program in the 2019-2024 RANHAM so that every Indonesian’s human rights receive perfect protection, in which the administrators of state power uphold human rights values in carrying out their duties to serve the community. Novelty/Originality: This research explored the local wisdom values of the DIY which can strengthen human rights values in Indonesia from various existing regulations in DIY with a broader approach, including raising local wisdom from human rights enforcement cases in Indonesia. Keywords: Constitutional Perspective, Human Rights, DIY’s Local Wisdom, Constitutional Court Decision No. 88/PUU-XIV/2016 ABSTRAK Tujuan: Penelitian ini bertujuan untuk (1) menggali nilai-nilai kearifan lokal Daerah Istimewa Yogyakarta (DIY) yang secara konstitusional dapat memperkuat nilai-nilai HAM di Indonesia dan (2) menganalisis pertimbangan hakim terhadap Putusan Mahkamah Konstitusi Nomor 88/PUU-XIV/2016 dari perspektif universalisme versus partikularisme hak asasi manusia di Indonesia. Metodologi: Penelitian hukum normatif ini menggunakan pendekatan filosofis dan perundang-undangan. Penelitian ini hanya menggunakan data sekunder yang terdiri dari bahan hukum primer dan sekunder yang disempurnakan melalui Focus Group Discussion. Data tersebut kemudian dianalisis dengan filosofi kualitatif deskriptif untuk menemukan makna dibalik objek yang diteliti melalui reduksi data, klasifikasi, interpretasi, penyajian, dan penarikan kesimpulan. Temuan: Kajian menunjukkan bahwa (1) nilai-nilai konstitusional HAM dalam kearifan lokal DIY dinyatakan secara eksplisit dalam Peraturan Daerah (Perda) dan Peraturan Daerah Khusus (Perdais) DIY. Kearifan lokal DIY dapat memperkuat nilai-nilai hak asasi manusia di Indonesia secara filosofis berdasarkan Pancasila dan menegaskan bahwa Pancasila sebagai identitas konstitusional merupakan kristalisasi adat budaya dan nilai-nilai agama di seluruh nusantara. (2) Pendapat hakim terhadap Putusan Mahkamah Konstitusi Nomor 88/PUU-XIV/2016 bersifat relatif-khusus; selain hak asasi manusia bersifat universal karena tidak ada perbedaan antara laki-laki dan perempuan untuk menjadi Gubernur Daerah Istimewa Yogyakarta, khusus Yogyakarta, tetap menjunjung tinggi nilai-nilai kearifan lokal sebagai syarat untuk menjadi Gubernur Daerah Istimewa Yogyakarta, di mana beliau akan menjadi raja yang bertahta Sultan Hamengku Buwono dan syarat menjadi Sultan didasarkan pada hukum internal turun temurun dari Kasultanan Ngayogyakarta Hadiningrat (Istana Yogyakarta) sejak tahun 1755. Kegunaan kajian: Penelitian ini diterapkan untuk (1) menjaga dan melestarikan nilai-nilai kearifan lokal Daerah Istimewa Yogyakarta (DIY) untuk penegakan hak asasi manusia di Indonesia sebagaimana diamanatkan oleh UUD 1945 dan (2) untuk mendukung program pemerintah dalam RANHAM 2019-2024 agar hak asasi manusia setiap orang di Indonesia mendapat perlindungan yang sempurna, di mana penyelenggara kekuasaan negara menjunjung tinggi nilai-nilai hak asasi manusia dalam menjalankan tugasnya melayani masyarakat. Kebaruan/Orisinalitas: Penelitian ini menggali nilai-nilai kearifan lokal Daerah Istimewa Yogyakarta (DIY) yang dapat memperkuat nilai-nilai HAM di Indonesia dari berbagai regulasi yang ada di DIY dengan pendekatan yang lebih luas, termasuk mengangkat kearifan lokal dari kasus-kasus penegakan HAM di Indonesia. Kata Kunci: Perspektif Konstitusi, Hak Asasi Manusia, Kearifan Lokal DIY, Putusan MK No. 88/PUU-XIV/2016